Tumor necrosis factor α antibody prevents brain damage of rats with acute necrotizing pancreatitis - Yang, Yan-Ling (World J Gastroenterol, 2004)
AIM: To study the protective effects of tumor necrosis factor α (TNFα ) antibody on pancreatic encephalopathy in rats. METHODS: One hundred and twenty SD rats were randomly divided into normal control group, acute necrotizing pancreatitis group and TNFα antibody treated group. Acute hemorrhage necrotizing pancreatitis model in rats was induced by retrograde injection of 50 g/L sodium taurocholate into the pancreatobiliary duct. Serum TNFα was detected and animals were killed 12 h after drug administration. Changes in content of brain water, MDA and SOD as well as leucocyte adhesion of brain microvessels were measured. RESULTS: In TNFα antibody treated group, serum TNFα level was decreased. Content of brain water, MDA and SOD as well as leucocyte adhesion were decreased significantly in comparison with those of acute necrotizing pancreatitis group (P < 0.05). CONCLUSION: TNFα antibody can alleviate the brain damage of rats with acute hemorrhage necrotizing pancreatitis.